The Time to Progression in Lung Adenocarcinoma Patients Receiving First- and Second-Generation EGFR-TKI in Indonesia - Syahruddin, Elisna; Soeroso, Noni Novisari; Ananda, Fannie Rizki; Wulandari, Laksmi; Setijadi, Ana Rima; Ermayanti, Sabrina; Pratiwi, Suryanti Dwi; Infianto, Andreas; Andayani, Novita; Munir, Sri Melati; Pratama, Avissena Dutha; Kusumawardani, Ida Ayu Jasminarti Dwi; Haryati, Haryati; Duyen, Natalie; Hanif, Muhammad Alfin; Lim, Darren Wan-Teck (Jurnal Respirasi, 2025)
Introduction: Targeted therapy, particularly epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI), is the first-line treatment for non-small cell lung cancer (NSCLC). However, drug resistance has grown in the last few decades. This study compared the progression time of lung cancer patients treated with first- and second-generation EGFR-TKI. Methods: Based on cytology and histological results, this cross-sectional study included 1,008 participants diagnosed with lung adenocarcinoma (LUAD) from 11 Indonesian Respiratory Centers. Every three months, the response to treatment was assessed using the Response Evaluation Criteria in Solid Tumours (RECIST) criteria in 1.1. Significant differences in the clinical features of the three TKI treatment groups were identified using logistic regression analysis, the median time to disease progression was estimated using the Kaplan-Meier technique, and independent prognostic factors related to the time to progression (TTP) were assessed using Cox proportional hazards regression. Results: This study examined 505 patients, the majority of whom were females (50.9%), never smoked (59.8%), diagnosed at an advanced stage (99.2%), and had an Eastern Cooperative Oncology Group (ECOG) scale of 0-1 (83.2%). Approximately 98.1% of patients were treated with afatinib (14.8%), erlotinib (18.6%), and gefitinib (66.1%) due to common mutations. The groups did not differ significantly (p>0.05). The median overall survival (OS) rate was 9 months. The time to LUAD progression in lung cancer was significantly impacted by poor performance (p=0.001). Conclusion: Epidermal growth factor receptor-tyrosine kinase inhibitor treatment can only prolong the TTP of LUAD by up to 9 months, and the performance scale when receiving the EGFR-TKI significantly affects the prognosis.